The Prevalence of Uropathogenic Escherichia coli Strains among Outpatients with Urinary Tract Infection in Zakho Hospitals-Zakho City, Duhok Province/ Iraq - Marwa Ibrahim; Haval Mohammed Khalid; Wijdan M S Mer (Al-Qadisiyah Journal of Pure Science, 2021)
This study involved the prevalence of uropathogenic Escherichia coli (UPEC) among outpatients of UTI attending three major hospitals in Zakho city. Four hundred urine samples were collected from patients of UTI of both sexes and different ages (≤ 1 year to over 50 years), during the period from July 2018 until January 2019. All urine samples were analyzed by conventional bacteriological method for the presence of Escherichia coli (E. coli), while molecular method was used for the presence of species-specific uidA gene in the isolated E. coli. Out of 400 samples, 141 (35.25%) were infected with UPEC from enrolled patients. The rate was higher in females than males (90.78% vs 9.22%), respectively. In both sexes, the age group 41-50 years in both sexes showed the highest rate (46.67%) of infection, and statistically this rate of infection was significant (p< 0.013) among both sexes and various age groups. Furthermore, in all ages, married patients showed slightly higher prevalence than un-married one (38% vs 32.5%), but this difference was statistically non-significant (p>0.05%). The rate of UTI was higher among urban inhabitants (40.56%) than others. During the months of the year, the peak (90.48%) in both sexes was during December while the lowest rates (13.64%) was during January.